QUANTITATIVE STUDIES OF THE VIRUS-HOST RELATIONSHIP IN CHIMPANZEES AFTER INAPPARENT INFECTION WITH COXSACKIE VIRUSES : I. THE VIRUS CARRIER STATE AND THE DEVELOPMENT OF NEUTRALIZING ANTIBODIES - Melnick, Joseph L. (The Rockefeller University Press, 1953)
Following oral administration of Coxsackie viruses (C viruses) to susceptible chimpanzees, these agents can be isolated from the throat for a period of approximately a week, from the blood for a few days, and from the stools for 2 to 3 weeks or even longer. Animals so infected respond with the formation of specific neutralizing antibodies which are maintained for at least 1 to 2 years. Such chimpanzees are immune when challenged orally with homologous strains of virus. They then excrete virus in the stools for 3 or 4 days (passive transfer); no virus can be recovered from the throats and blood of these animals, and neutralizing antibody levels remain unchanged. Animals immune to one antigenic type of C virus can be infected by feeding a different antigenic type. Following such a heterotypic challenge, virus can again be isolated from the throat, blood, and stools; neutralizing antibodies develop to the new strain. Antibodies to the Texas-1 type of C virus were already present in four chimpanzees upon their arrival in the laboratory from Africa. It was possible to set up intestinal carriage of the Texas-1 virus in these animals and to demonstrate a 10- to 100-fold increase in titer of neutralizing, as well as complement-fixing, antibody. Quantitative titrations of the amount of virus present in the stools and throat were performed. Immediately after the first feeding of virus relatively large amounts can be detected in the stools; the titer drops, but may be maintained for as long as 25 days at 10(–2) to 10(–3), furnishing evidence that virus multiplication has taken place. Virus in the throat reached the same order of magnitude at first as in the stools but there was a rapid decline to zero in a few days. The Ohio-1 virus differed from the others in that it persisted in the throat as long as in the stools, and in several instances reached a higher titer in the throat. Following homotypic challenge with all types, virus could be detected in the stools for only a relatively short period of time and at low concentration. Virus-neutralizing substances could not be detected in the stools or throat swabs of convalescent animals, at a time when their serum-neutralizing antibody titers were high. Under the limited conditions of the present experiments, C viruses had no effect on the infection of chimpanzees with three different antigenic types of poliomyelitis virus. Both poliomyelitis and C viruses set up independent infections without apparent interaction between them. No enhancement of the poliomyelitis infection took place, as was plain from the fact that none of the infected chimpanzees became paralyzed. a titration of Texas-1 C virus in four chimpanzees revealed that a suspension of infected tissue diluted to 10(6.0) could cause the development of the carrier state; accidental infection of control animals with other Coxsackie types indicated also that very little virus may be necessary to initiate infection. Seven distinct antigenic types of C virus were inoculated subcutaneously and intramuscularly at the same time into four chimpanzees. The response was the same as that following feeding; virus could be recovered from the throat, blood, and stools, and the animals developed neutralizing antibodies to all seven types of C virus. There was no detectable interference among the viruses. Cortisone did not bring about the reappearance of the virus excretion in chimpanzees previously infected and shown to be intestinal carriers of poliomyelitis and Coxsackie viruses.